Singlehood in Hadiths: Takhrij Hadith and Contextual Approach - Khaerul Umam; Atiyatul Ulya; Shahir Fikri (FIQHUL HADITS : Jurnal Kajian Hadits dan Hukum Islam, 2026)
This research is motivated by the declining marriage rate in the contemporary era due to a shift in orientation among Gen Z and Millennials. So that not marrying (singlehood) has become a trend and a life principle. This problem seems to be at odds with the hadith of the Prophet Muhammad SAW which in his narration forbids someone from being single (tabattul). Therefore, this study aims to determine the quality of the hadith about tabattul which is then relevant to the phenomenon of singlehood that is rampant lately. This research uses a qualitative method with a type of literature study, the problems and hadith in this study are examined using a takhrij approach that includes criticism of sanad and matan within the scope of discussion of Sufism and psychology. The results obtained from this study are first, the quality of the hadith about tabatuul has authentic quality (H.R Al-Bukhari No. 5073), this is illustrated by the results of the takhrij which shows the presence of syawahid and tawabi. In addition, the sanad of the hadith is connected and has a fair and strong narrator of memorization, then the hadith also does not contradict the Qur'an. However, from a Sufi perspective, the term "tabattul" differs from the "uzlah" practiced by Sufis. Meanwhile, from a psychological perspective, the term "tabattul" in the hadith can be equated etymologically with the phenomenon of singlehood, as both involve the absence of a romantic relationship. Ultimately, according to the hadith, "tabattul" is permissible if there is a valid Islamic excuse. However, singlehood is prohibited if the reason is for promiscuity, partying, or a reluctance to follow the Sunnah of the Prophet Muhammad.